Analisis kinerja profitabilitas Bank Aceh Syariah melalui Return on Assets (ROA) periode 2020–2024 - Fitriah, Destiana Mahmudatul; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study examines Bank Aceh Syariah's profitability using the Return on Assets (ROA) ratio as the primary proxy for the period 2020 to 2024. Secondary data is drawn from Bank Aceh Syariah's officially published annual financial reports and the Financial Services Authority (OJK)'s Sharia Banking Statistics publication. The approach used is a quantitative descriptive analysis based on time trends. The findings indicate a significant increase in ROA from 1.73% (2020) to 2.05% (2022), then remained stable at 2.01% in 2023 and 2024. The surge in 2021–2022 reflects the successful post-pandemic economic recovery, maintained financing quality, and increased operational efficiency. The consistent ROA at 2.01% in subsequent periods was maintained thanks to a very low level of non-performing financing (averaging 0.34%), a capital adequacy ratio (CAR) above 20%, and prudent liquidity management. Overall, Bank Aceh Syariah's ROA significantly exceeds the national average for Islamic banking (1.1%–1.5%), placing it among the most profitable Islamic banks in Indonesia. This study concludes that Bank Aceh Syariah was able to maintain strong and sustainable profitability performance throughout 2020–2024.